Amber the orange fairy - Meadows, Daisy; Ripper, Georgie (New York : Scholastic, 2003)
Friends Rachel and Kirsty, vacationing with their parents on Rainspell Island, continue their search for the rainbow fairies who have been banished from Fairyland by Jack Frost, and succeed in finding Amber, the second of the seven magical sisters, who is trapped in a seashell.
"A Little Apple paperback."
3.5
K-3
K-3
500
Keywords: Fairies -- Juvenile fiction; Rainbows -- Juvenile fiction; Color -- Juvenile fiction; Fairies -- Fiction; Rainbows -- Fiction; Color -- Fiction; Fantasy; Fairies -- Fiction; Rainbow -- Fiction; Color -- Fiction; Fantasy fiction; Fantasy fiction